PENGARUH OTONOMI KERJA TERHADAP LOCUS OF CONTROL DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI (Pada Kantor Dinas Pendidikan Provinsi Aceh) - Syarfun Huda; Saiful Bahri (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research aims to know the influence of work autonomy against the locus of control with job satisfaction as mediation. The sample used in this study was a civil servant in the office of the Aceh provincial office of education. This research method using the questionnaire as an instrument of research. A questionnaire spread out as much as 113 questionnaires. Sampling technique used was stratified probability sampling. Hierarchical Linear Modelling (HLM) is used as a method of analysis to find out the influence of variable involved. The results showed that (1) influential work autonomy significantly to locus of control, (2) job satisfaction the significant effect against the locus of control, (3) influential work autonomy significantly to job satisfaction, (4) autonomy of work influence on locus of control with job satisfaction as mediation.